Causes behind gender difference in mathematics: an exploratory study in BRAC schools - Shahjamal, Mirja Mohammad (BRAC Research and Evaluation Division (RED), 2020)
This dissertation explores the causes behind gender difference in BRAC schools .The problem was derived from previous studies, which confirm gender difference in mathematics in BRAC schools. Exploratory as well as qualitative research strategy was used for the purpose. Because, such strategy was thought suitable to find out the causes and the causes behind the causes of the problem from different points of view. The study was .... conducted in three BRAC schools, situated in a remote rural area of Bangladesh. The data were collected mainly from classroom observation. Besides, the students, parents, teachers programme organizers, teacher trainer and other concerned persons were interviewed. Six case studies were also done. All the data were collected by the researcher. Although overall teaching learning process in BRAC schools was satisfactory towards quality education but evidence of gender discrimination was in place. The main causes of gender difference in mathematics are the deprivation of the girls in family, society and schools, discriminatory attitude to the girls by the teachers and the peer boys, and the inside weaknesses of the BRAC school programme. Gender imbalance against girls ·is a serious issue in the present day world including Bangladesh. Some recommendations are made in order to remove the gender gap in mathematics in BRAC schools.